The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1088/1361-6641/ac461f
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy and robustness of RRAM-based in-memory computing against RRAM hardware noise and adversarial attacks

Abstract: We present a novel deep neural network (DNN) training scheme and RRAM in-memory computing (IMC) hardware evaluation towards achieving high robustness to the RRAM device/array variations and adversarial input attacks. We present improved IMC inference accuracy results evaluated on state-of-the-art DNNs including ResNet-18, AlexNet, and VGG with binary, 2-bit, and 4-bit activation/weight precision for the CIFAR-10 dataset. These DNNs are evaluated with measured noise data obtained from three different RRAM-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…IMC architectures are known for their improved energy efficiency and throughput, but they have some drawbacks. One such drawback is the limited precision of the IMC crossbar array, particularly in the memory cell and ADC, which can affect the accuracy of DNN inference [74,75]. Additionally, noise within analog computation can also harm DNN inference accuracy.…”
Section: Challenges With Imc Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…IMC architectures are known for their improved energy efficiency and throughput, but they have some drawbacks. One such drawback is the limited precision of the IMC crossbar array, particularly in the memory cell and ADC, which can affect the accuracy of DNN inference [74,75]. Additionally, noise within analog computation can also harm DNN inference accuracy.…”
Section: Challenges With Imc Architecturesmentioning
confidence: 99%
“…In [76], VAT is combined with dynamic precision quantization to mitigate the post-mapping accuracy loss. Another approach proposed in [75] involves injecting RRAM macro measurement results that include variability and noise during the DNN training process to improve the DNN accuracy of the RRAM IMC hardware. Mohanty et al [88] proposes post-mapping training by selecting a random subset of weights and mapping them to an on-chip memory to recover the accuracy.…”
Section: Block Diagram Of a Sram-based Imc Crossbar Array An Array Of...mentioning
confidence: 99%
“…While this work performs experiments using noise models obtained from various SRAM arrays, it still lacks a full-fledged hardware demonstration. Cherupally et al ( 2021 ) obtain a noise model of a RRAM-based crossbar often found in analog in-memory computing architectures. The noise model is then used in simulation to study the adversarial robustness of neural networks deployed on such a crossbar.…”
Section: Related Workmentioning
confidence: 99%
“…Read et al [ 10 ] reverse engineered the weights and biases of DNN models mapped on analog CIM systems. Cherupally et al [ 11 ] studied adversarial attacks on analog RRAM‐based CIM systems. In this study, we analyze CIM privacy breach vulnerabilities by reconstructing users’ private input data from power side‐channel profiling of CIM systems.…”
Section: Introductionmentioning
confidence: 99%